If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 3y + -2z = -12 Solving 6x + 3y + -2z = -12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. 6x + 3y + -3y + -2z = -12 + -3y Combine like terms: 3y + -3y = 0 6x + 0 + -2z = -12 + -3y 6x + -2z = -12 + -3y Add '2z' to each side of the equation. 6x + -2z + 2z = -12 + -3y + 2z Combine like terms: -2z + 2z = 0 6x + 0 = -12 + -3y + 2z 6x = -12 + -3y + 2z Divide each side by '6'. x = -2 + -0.5y + 0.3333333333z Simplifying x = -2 + -0.5y + 0.3333333333z
| -6(-4x-4y)-3(y-5x)= | | 7w+4w-10=2w | | -5(x-11)=48-22(x-5) | | 7(-5+m)=0 | | 5x-3(x-10)+1=-(x-5)+20 | | 15x+24=8*(10+3x)-2 | | 20k=-260 | | -4(x+3)=-3(x+7) | | 2X+9=-7X+63 | | 9+2.3x=1+x | | -3w-3(4z-4w)+2z= | | 3(x-2)-1=5x-7-2x | | -11x+6x-24=56 | | -18-6(-1)=6(1+3(1)) | | 5x+5=10x+15 | | 8x+11=3x+9 | | x=30-3x | | -66+7x=22-x | | 5-7x=x-35 | | -3x-12=28-x | | 13=4-11 | | 3x=4y-7 | | 3p+q-p+2q= | | (7x-1)=(11x+19) | | 1.25r-7=-11 | | 5y-18=2 | | 5x-8=13+7*(x-3) | | 1.25-7=-11 | | 2x^2+5x-176=0 | | 77-4x=5x+24 | | 8(x+1)-2=3x-4(2-2x) | | 2x+7x+8=x-14 |